Phacolytic glaucoma: visual outcome - Peram, Venkataratnam; Atti, Srihari; Mahendra, Superna (International Journal of Research in Medical Sciences, 2017)
Background: This study was conducted to evaluate the visual outcome of phacolytic glaucoma, a common cause of ocular morbidity. Methods: Participants were 30 patients in a tertiary care hospital for both urban and rural population. 30 eyes of patients clinically diagnosed as phacolytic glaucoma were treated. Demographic data and duration of the symptoms of the patients before presenting to the hospital were noted. Intraocular pressure (IOP) and visual acuity were recorded preoperatively and postoperatively. Small Incision cataract surgery with posterior chamber intraocular lens implantation (IOL) was done after the control of intraocular pressure and inflammation. Postoperative complications were noted. The data was analyzed by simple statistical methods. Results: Age group distribution was 19 (63.3%) in >50-60 yrs, 9 (30.0%) in >60-70 yrs and 2(6.4%) in >70 yrs. Sex distribution was 21 (70.0%) of males and 9 (30.0%) of females. Mean age of the all the patients was 60.7 yrs (males 59.95 yrs and females 62.6 yrs). Laterality was RE in 16 (70.9%) and LE in 9 (30.0%). Duration of the presenting symptoms before reporting to the hospital was <1 week in 17 (56.6% and >1 week in 13 (43.3%). Mean IOP was 45.8 mmHg preoperatively. Visual Acuity was PL doubtful in 2 (6.6%), PL +ve in 15 (50.0%) and HM<3/60 in 13 (43.4%) preoperatively. Postoperative visual acuity at 6-8 weeks was <6/60 in 8 (26.7%) and >6/60 in 22 (73.3%). Postoperative complications were bullous keratopathy in 5 (16.6%), anterior uveitis with membrane on IOL in 7 (23.3%), posterior capsular tear in 3 (10.0%) and Zonular dialysis in 2 (6.6%). Fellow eye showed pseudophakia in 22 (73.4%), immature cataract in 6 (20.0%) and Aphakia in 2 (6.6%). Conclusions: This study concludes that a better Visual outcome in phacolytic glaucoma depends on the effective Preoperative control of intraocular pressure and inflammation.